The Relative Importance of Computer Self-efficacy, Perceived Ease-of-Use and Reducing Search Cost in Determining Consumers’ Online Group-buying Intention - Jeng, R.; Tseng, S.M. (International Journal of Human and Technology Interaction (IJHaTI), 2018)
In order to shop in the online groupbuying (OGB) websites, consumers should have a certain ability to utilize computer and the Internet. Therefore, this study explores the relative importance of computer self-efficacy and perceived ease-of-use in determining consumers’ OGB intention. Moreover, different from the direct online shopping, OGB would allow the group of consumers to get a special discount, and incentives for saving money are more likely to characterize the major concern of consumers’ engaging in OGB. This study thus further explains the effect of reducing search cost on OGB intention. The result shows that computer self-efficacy has an indirect influence on customers’ intention to use OGB through the mediation of perceived ease-ofuse; while, reducing search cost is an important factor that directly affects customer’ intention to use OGB. This approach provides valuable suggestions that allow OGB vendors to enhance customers’ OGB intention.